ANALYSIS OF FINANCIAL LITERACY TRENDS - Čaplinska, Aina; Stašāne, Janīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The following skills, such as planning of personal finances, formation and diversification of savings, augmentations of personal capital and open-mindedness to new initiatives in entrepreneurship activities, enhance financial sustainability of the population, and are decisive for the quality of life. Every person in certain circumstances can be financially and economically active, if he/she has got such a competence as financial literacy, which is much more important in the course of life than a level of income or professional qualifications, because, hereafter the governing factor will be not a possession of financial instruments by the person, but skills of the effective management for an achievement of own objectives. The aim of the research – to analyse the financial literacy of young people in Daugavpils.Methods used in the research: the monographic method – a theoretical description of financial literacy, the graphical method – a graphical representation of obtained results, the interview method (questionnaire) –  data acquisition required for the research, the statistical method–analysis of statistical information, the comparative method – a description of obtained data and drawing conclusions. The financial literacy of Daugavpils youth has been researched and evaluated.